Nutritional And Anti-Nutritional Analysis Of Some Selected Microgreens (Applied Biological Research, 2019)
Microgreens are immature greens of edible vegetables and herbs which may  serve as a good nutrient source. The present study was conducted on ten  locally available plants, tested as microgreens. The study included evaluation  of seed germination and growth pattern for two weeks period and nutritional  characterization of selected microgreens. Results showed that the seeds of  selected plants had > 80% germination and attained 6-7 cm height within  two weeks. Vitamin C was high in all the microgreens tested; while thiamine,  riboflavin and niacin were high in microgreens of Amaranthus viridis, Vigna  radiata and Allium cepa, respectively. However, vitamin content was higher  in sprouts than microgreens and mature edible parts of selected plants even  though some exceptions were found. Anti-nutrients analyzed in microgreens  were below the toxic levels. Microgreens had low carbohydrates and anti nutrient contents; but high vitamin contents, so these can be recommended  as dietary supplement, especially for those who preferred less carbohydrate containing food supplements.
Keywords: Growth-pattern; microgreens; nutritional analysis; seed germination; vitamins